Atomic force microscopy studies of bioprocess engineering surfaces – imaging, interactions and mechanical properties mediating bacterial adhesion. Issue 7 (10th May 2017) - James, Sean A.; Hilal, Nidal; Wright, Chris J.
Abstract: The detrimental effect of bacterial biofilms on process engineering surfaces is well documented. Thus, interest in the early stages of bacterial biofilm formation; in particular bacterial adhesion and the production of anti‐fouling coatings has grown exponentially as a field. During this time, Atomic force microscopy (AFM) has emerged as a critical tool for the evaluation of bacterial adhesion. Due to its versatility AFM offers not only insight into the topographical landscape and mechanical properties of the engineering surfaces, but elucidates, through direct quantification the topographical and biomechnical properties of the foulants The aim of this review is to collate the current research on bacterial adhesion, both theoretical and practical, and outline how AFM as a technique is uniquely equipped to provide further insight into the nanoscale world at the bioprocess engineering surface. Abstract : Atomic force microscopy (AFM) has emerged as an essential tool for the characterization of bioprocess surfaces and the evaluation of bacterial adhesion, a key problem that compromises process efficiency. The versatility of AFM offers not only insight into the topographical landscape and mechanical properties of the engineering surfaces, but elucidates, through direct quantification the topographical and biomechanical properties of surfaces such as microbial foulant layers. The aim of this review is to collate the current research on bacterial adhesion, both theoretical and practical, and outline how AFM as a technique is uniquely equipped to provide further insight into the nanoscale world at the bioprocess engineering surface.